(untitled) (Research, Society and Development, 2020)
Objectives: The present study aims to investigate the development of MME loss in individuals undergoing bariatric surgery using bioimpedance. Method: Retrospective and observational cohort study, data were only collected and analyzed after approval by the Research Ethics Committee. The patients included were followed up with clinical and bioimpedance assessments for at least 6 months. The variables of interest were: epidemiological, anthropometric, pre- and post-surgery data, and results of serial bioimpedances. The data are presented in relative and absolute frequency, the comparison of means was done by the Student’s T test. The average survival time until the development of low MME was estimated by the Kaplan-Meier model. Α = 5% was defined. Results: 30 patients were included, 80% of whom were female. The sample had an average age of 39 years. An average difference of 27.4 kg in body mass was found, when compared to the last anthropometric assessment with the values ​​prior to surgery, which proved to be statistically significant (p <0.001). The average MME in the first post-surgical bioimpedance was 27.5 kg. After a period of 6 months, the individuals were again evaluated and had an average of 26.7 kg, the loss of MME was statistically significant (p = 0.033). It was observed that 20% of the individuals had MME values ​​below the lower limit of normality, the Kaplan-Meier survival model estimates an incidence of 40% of this outcome in 30 months of follow-up. Conclusion: Patients undergoing bariatric surgery demonstrate a greater risk of developing nutritional deficiencies, mainly due to the excision of structures that impair nutrient absorption. Protein deficiency resulting from this process can manifest itself with reduced MME.